2009
DOI: 10.1016/j.mce.2009.07.001
|View full text |Cite
|
Sign up to set email alerts
|

Regulation of osteoblastogenesis and osteoclastogenesis by the other reproductive hormones, Activin and Inhibin

Abstract: SummaryThere is both cellular and physiological evidence demonstrating that both Activins and Inhibins regulate osteoblastogenesis and osteoclastogenesis, and regulate bone mass in vivo. Although Activins and Inhibins were initially isolated from the gonad, Activins are also produced and stored in bone, whereas Inhibins exert their regulation on bone cell differentiation and metabolism via endocrine effects. The accumulating data provide evidence that reproductive hormones, distinct from classical sex steroids… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
46
0
2

Year Published

2010
2010
2019
2019

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 48 publications
(48 citation statements)
references
References 112 publications
0
46
0
2
Order By: Relevance
“…In vivo, TGFb does not prevent bone loss induced by ovariectomy (76) but prevents immobilization-related bone loss caused by decreased osteoblastogenesis (77,78). Inhibins (Inh), activins, and myostatins (GDF8) are other members of the TGFb superfamily that control bone metabolism (79). InhA overexpression was found to prevent gonadectomyinduced bone loss (80).…”
Section: Growth Factorsmentioning
confidence: 99%
“…In vivo, TGFb does not prevent bone loss induced by ovariectomy (76) but prevents immobilization-related bone loss caused by decreased osteoblastogenesis (77,78). Inhibins (Inh), activins, and myostatins (GDF8) are other members of the TGFb superfamily that control bone metabolism (79). InhA overexpression was found to prevent gonadectomyinduced bone loss (80).…”
Section: Growth Factorsmentioning
confidence: 99%
“…BMPs therefore can utilize ACVR2A/B and also the BMP-specific type 2 receptor, BMPR2, allowing for potential competition for ACVR2A/B by BMPs and activin based on the availability of BMPR2. We examined this hypothesis in the context of the mouse skeleton, taking advantage of the fact that postnatal bone formation and mineralization is under tight reciprocal regulation by BMPs and activins (Alves et al, 2013;Eijken et al, 2007;Fajardo et al, 2010;Ikenoue et al, 1999;Koncarevic et al, 2010;Li et al, 2013;Lotinun et al, 2010;Matsumoto et al, 2012;Mishina et al, 2004;Nicks et al, 2009;Pearsall et al, 2008;Perrien et al, 2007;Ruckle et al, 2009;Sakai et al, 2000;Sherman et al, 2013;Simic et al, 2006;Zhang et al, 2009;Zhao et al, 2002). Surprisingly, engineering specific deletion of BMPR2 in bone-forming cells (Bmpr2-cKO mice) selectively reduces activin pathway activation but has no apparent effect on BMP signaling.…”
Section: Introductionmentioning
confidence: 99%
“…In addition to storage in the bone matrix, ActA is an endogenous growth factor produced during ex vivo bone marrow cell osteoblast development, where it has the ability to enhance the formation of both bone forming osteoblasts and bone resorbing OCLs (Fuller et al, 2000;Gaddy-Kurten et al, 2002;Nicks et al, 2009;Silbermann et al, 2014). This appears to be the case in humans, and several investigators have suggested an important role for ActA in the fundamental process of bone remodeling (Pearsall et al, 2008;Teitelbaum and Ross, 2003), which is responsible for the maintenance of skeletal integrity (Suva et al, 2011).…”
Section: Introductionmentioning
confidence: 99%